MEMBANGUN KESADARAN HUKUM BERBASIS KEADILAN RESTORATIF DI TINGKAT DESA - Arka Atyanta; Arif Awaludin; Ikama Dewi ST (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service Program (PKM) was conducted as a contribution of the Faculty of Law, Universitas Wijayakusuma Purwokerto, in enhancing legal awareness among the community of Wlahar Wetan Village, Patikraja District, Banyumas Regency. The village community has long relied on informal conflict resolution while neglecting victim protection. Therefore, a more humanistic approach that focuses on restoration rather than punishment, namely restorative justice, is urgently needed. This program aims to improve the community’s understanding of lawful and fair conflict resolution mechanisms, strengthen the role of village officials and community leaders as facilitators of mediation, and develop a community-based model for resolving disputes at the village level. The methods included interactive legal education, case discussion and consultation, simulated restorative mediation, and community assistance in establishing the Village Restorative Forum (FRD). The results show increased legal knowledge and awareness among the community, enhanced capacity of village officials and local leaders in carrying out restorative-based mediation, and a shared commitment to institutionalize restorative justice principles through the establishment of the FRD. This program emphasizes that law should function not only as an instrument of punishment but also as a means of restoring harmony within society. By strengthening a restorative legal culture, the community is expected to resolve conflicts independently, promptly, and fairly in accordance with local wisdom values. This program serves as an initial step toward transforming a more humanistic and sustainable community legal culture.